Blood flow restriction exercise in sprinters and endurance runners - Takada, S.; Okita, K.; Suga, T.; Omokawa, M.; Morita, N.; Horiuchi, M.; Kadoguchi, T.; Takahashi, M.; Hirabayashi, K.; Yokota, T.; Kinugawa, S.; Tstsui, H. (Journal of Sports Sciences, 2012)
Abstract Purpose: We demonstrated that blood flow restriction (BFR) remarkably enhances muscular metabolic stress in resistance exercise, although there is a wide range of individual differences in the responses. It is possible that these differences could be due to training status and muscular physiological characteristics. We investigated intramuscular metabolic responses during low-intensity resistance exercise with BFR between two different types of track athletes.